New Aminocoumain as Corrosion Inhibitor - Al-Majedy, Yasameen K (Al-Nahrain Journal of Science, 2018)
New green organic molecules as corrosion inhibitor namely, 2-amino-4-(4-nitrophenyl)-3-cyano-4, 5-dihydropyrano (3,2-c) coumarin (AND) was synthesized starting from 4-hydroxycoumarin, malonitraile and 4-nitrobenzaldehyde and tested on mild steel (MS) in 1 M HCl media by a weight loss method and identification of the surface technique employee scanning/electron/microscope (SEM) studies. The AND as an inhibitor compound have been elucidate spectroscopically (FT-IR ,1HNMR and 13CNMR) The weight loss investigation demonstrated that inhibition performances have been improved via concentration raising of inhibitor. To support our results scanning electron microscopy was employed to clarify the surface of the MS with and without AND in 1.0 M HCl media. The inhibition performance rate was 96% at the maximum utilized concentration of AND